Impact of responsible hunting on sustainable wildlife ranching - van de Giessen, Johann, author; Nel, Lizanne, author; International Wildlife Ranching Symposium, publisher (Colorado State University. Libraries, 2016)
Recent studies on the economic contribution of hunting to the GDP of African countries where hunting takes place, put it at over a billion US$ annually, contributing in excess of 50 000 jobs. Looking at South African specifically, visiting trophy hunters and local consumptive hunters alternatively contribute over US$ 200 million and over US$ 600 million to the South African GDP, almost 10% of the total tourism GDP contribution, with processed products contributing an additional US$ 300 million annually. Sustainable and responsible hunting clearly contributes to the Millennium Development Goals of the UN, and has the potential to increase this contribution, to illustrate: the consumptive hunting GDP contribution in South Africa has grown by35% from 2013 to 2015.Hunting incentives extensive wildlife ranching, contributing to its profitability, contributing to ecosystem services. These extensive areas has the potential to contribute 43 job opportunities per1000 Ha, of which 17 will be permanent jobs, while mostly maintaining the ecological integrity of the area. Extensive wildlife ranching may in the long run compete with mining as a viable alternative land use option. However there are risks that may prevent the positive contributions from realizing, like an unsupportive regulatory environment, unsustainable ranching practices, environmental and climatic changes, reputational risks associated with national and international views on current hunting practices. Management of these risks can include the development of industry standards, an effective green certification or labelling scheme and common sense and uniform regulations.
The benefits of responsible hunting to sustainable wildlife ranching
Presented at the 9th international wildlife ranching symposium: wildlife - the key to prosperity for rural communities, held on 12-16 September 2016 at Hotel Safari & the Safari Court, Windhoek, Namibia.